2013
DOI: 10.1051/0004-6361/201220210
|View full text |Cite
|
Sign up to set email alerts
|

The VLT-FLAMES Tarantula Survey

Abstract: Context. The Tarantula Nebula (a.k.a. 30 Dor) is a spectacular star-forming region in the Large Magellanic Cloud (LMC), seen through gas in the Galactic disc and halo. Diffuse interstellar bands (DIBs) offer a unique probe of the diffuse, cool-warm gas in these regions. Aims. The aim is to use DIBs as diagnostics of the local interstellar conditions, whilst at the same time deriving properties of the yet-unknown carriers of these enigmatic spectral features. Methods. Spectra of over 800 early-type stars from t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 67 publications
4
62
1
Order By: Relevance
“…We see the young stars have similar reddening to the RC stars and use them to examine the relationship between A V and DIB equivalent width using data from the FLAMES Tarantula survey (van Loon et al 2013) finding similar results to what they found when using O-and B-type stars. This shows it is possible to use other populations to supplement the reddening map.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…We see the young stars have similar reddening to the RC stars and use them to examine the relationship between A V and DIB equivalent width using data from the FLAMES Tarantula survey (van Loon et al 2013) finding similar results to what they found when using O-and B-type stars. This shows it is possible to use other populations to supplement the reddening map.…”
Section: Discussionsupporting
confidence: 72%
“…The K s passband curve begins before the K passband, finishes before it and the overall width is nearly identical. The extinction coefficients do vary slightly with spectral type (van Loon et al 2003). This variance is small in the NIR (0.004 mag from A0 to M10 star in the J band).…”
Section: Appendix B: Extinction Lawsmentioning
confidence: 92%
See 2 more Smart Citations
“…Most measured DIBs have a Galactic origin. Still, they have also been detected in the Magellanic clouds, M31 and M33 (Ehrenfreund et al 2002;Welty et al 2006;Cordiner et al 2008aCordiner et al , 2008bCordiner et al , 2011van Loon et al 2013) and in a few line of sights toward e.g., starburst galaxies or in SNe Ia spectra (Sollerman et al 2005;Cox & Patat 2008;Heckman & Lehnert 2000;Phillips et al 2013). Recently a DIB gradient was established for the first time in a 160 Mpc distant galaxy (Monreal-Ibero et al 2015).…”
Section: Introductionmentioning
confidence: 95%